Should the Global Community Welcome or Mourn New Oil Discoveries? - Alfons Weichenrieder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Focusing on the change in pollution, consumption and extraction cost paths, we build a multi-period model that allows us to assess whether oil windfalls may be globally welfare-enhancing. The assessment depends on the quality of the discovered resource, expressed as the extraction cost. Our findings suggest that even when faced with high environmental externalities and no internalization mechanism for them, new oil finds can be conducive to welfare.
Keywords: 330